Application of Saponins from Ambon Banana Petiole (Musa paradisiaca var. sapientum L.) as Natural Surfactants in Bio-Hand Soap - Dini Nur Afifah; Rahma Falah Maulidina; Novi Astuti; Riska Annisa Wahyadi (Research in Chemical Engineering, 2023)
Surfactants are commonly use as a foaming agents contained in soap products. Consequently, the type of surfactant used is a synthetic product that is difficult to degrade by nature fate. In addition to environmental problems, prolonged use of these products can cause health problems, such as irritation in the form of dry, scaly, itchy skin, to red rashes. Synthetic surfactants used in industry are also petroleum derivatives. This fact makes the sustainability of the industry threatened due to the increasingly critical oil reserves. Based on these problems, it is important to study alternative synthetic surfactants that are more environmentally friendly, safe for health, and abundantly available in nature. In this study, the potential of saponins from the petiole of the Ambon banana (Musa paradisiaca var. sapientum L.) was studied as a natural surfactant in hand soap (bio-hand soap). The purpose of this study was to study the effect of the variable concentration of ethanol solvent and immersion time on the amount of saponin extract yield and the formulation of bio-hand soap. The results showed that the highest extract yield of Ambon banana petiole extract could be achieved using ethanol solvent at a concentration of 80% and a maceration time of 48 hours. Based on the quality tests on bio-hand soap products that have been carried out, formula 1 (20% saponins), 2 (30% saponins), and 3 (40% saponins) have color, shape, anti-bacterial agent, and pH values that are following SNI 2588:2017. The formula that is considered the most optimum for the production of bio-hand soap is Formula 2. This is based on the highest foam stability value, which is 67.56%.